A novel DNA binding protein-based platform for electrochemical detection of miRNA. Issue 18 (4th August 2021) - Umer, Muhammad; Aziz, Nahian B.; Mahmudunnabi, Rabbee G.; Shim, Yoon-Bo; Salomon, Carlos; Shiddiky, Muhammad J. A.
Abstract : We present a DNA binding protein-based novel amplification-free sandwich type platform assay for electrochemical detection of miRNA. Abstract : We present a novel amplification-free sandwich type platform assay for electrochemical detection of miRNA. The assay is based on T4 DNA polymerase mediated synthesis of the p53 binding DNA sequence at the 3′ end of target miRNA. The resulting miRNA-DNA chimera is detected via an electrochemical sandwich hybridization assay where HRP-labelled p53 binds to its recognition sequence and an amperometric signal is generated by hydroquinone-mediated enzymatic reduction of H2 O2 . The limit of detection of our assay was estimated to be 22 fM with a linear dynamic range of 100 fM–1 nM. This new platform method of detecting miRNA shows superior performance to conventional electrochemical miRNA biosensors and has the potential for amplification-free analysis of miRNA with high specificity and sensitivity.